Impacts of Stress Response and Negative Emotion on Mental Health of College Students During the COVID-19 Outbreak - Xu, Fuming; Huang, Long (Frontiers in Psychiatry, 2022)
Object: In this study, we aimed to explore the influences of stress responses and negative emotion on mental health of college students during the initial COVID-19 outbreak in China. Methods: A nationally representative sample of 1,351 college students, aged 18-23 years, took part in an online survey during the COVID-19 outbreak. The ANOVA, correlation coefficients, structural equation modeling (path analysis), and other statistical analysis methods were used for data analysis. Results: (1) The Chinese college students’ epidemic panic and cognitive evaluation were found to be moderate (3.73±0.74, 3.76±0.62), while their defensive response was higher (4.61±0.55). Their mental health during the COVID-19 outbreak was found to be good (3.75±0.76). (2) The quality of their mental health was significantly and negatively associated with epidemic panic, and the quality of their mental health was significantly and positively associated with defensive response. (3) The quality of their mental health was significantly and negatively associated with negative emotion. (4) College students' epidemic panic and defensive response to the COVID-19 had a directly predictive effect on their mental health. Conclusion: College students' negative emotion played a partial mediating role in the relationship between epidemic panic and mental health. College students' negative emotion played a complete mediating role in the relationship between cognitive appraisal and mental health.